Electrochemical Activity of Cytochrome P450 1A2: The Relevance of O2 Control and the Natural Electron Donor. Issue 3 (19th January 2021) - Silveira, Célia M.; Rodrigues, Patrícia R.; Ghach, Wissam; Pereira, Sofia A.; Esteves, Francisco; Kranendonk, Michel; Etienne, Mathieu; Almeida, M. Gabriela
Abstract: Invited for this month's cover picture is the Group of Biomarkers and Biosensors – GB2 (https://gb29.webnode.pt ) at Universidade NOVA de Lisboa (Portugal) and CiiEM (Portugal). The cover picture shows the electrochemical response of the human monooxygenase enzyme, cytochrome P450 1A2 (CYP1A2), in the presence of its natural electron donor partner, cytochrome P450 oxidoreductase (CPR), highlighting the role of the interaction with the latter in the stabilization of CYP1A2 and attaining the electrochemically driven activity towards O2 . The picture also emphasizes the protein entrapment matrix, a biocompatible sol‐gel film, which proved to be crucial for the achievement of interfacial electron transfer. Read the full text of the Article at 10.1002/celc.202001255 . Abstract : "This paper describes the study of the electrochemical behavior of cytochrome P450 1A2 (CYP1A2) in the presence and absence of its natural electron donor, cytochrome P450 oxidoreductase (CPR), emphasizing the relevance of the enzyme's redox partner and the O2 control in the electrocatalytic activity…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding article on 10.1002/celc.202001255